The Influence of Brand Image and Service Quality on Purchasing Decisions - Abdul Rouf; Wishnu Anugrah Wahyu Saputra (DEAL: International Journal of Economics and Business, 2024)
In economic development in this modern era, consumers are very critical in making decisions to buy products. This can be seen in line with the rapid development in the business world, where more and more business people are opening and developing their businesses. The tight competition and the increasing consumer expectations for a product, especially service products, make companies have to have their own ways to improve their services and sales. One of the service products that is increasing in this modern era is the coffee shop business. Where each company is required to have its own uniqueness that can attract the attention of consumers to maintain or seize the existing market. The purpose of this study was to determine. the influence of Brand Image variables and service quality on purchasing decisions on coffee memories quantitative method, The population sampling method used is all students of Universitas Pelita Bangsa or people who have visited the coffee shop memories, so it can be said that the population is non-probability sampling, so it does not provide opportunities or opportunities for sampling respondents, namely incidental. The data processed is primary data obtained from the results of distributing questionnaires with 74 respondents. Data analysis using the PLS 3 (Partial Least Square) program. The results of the research analysis, the indicators in this study are valid. Brand Image variable (X1) has a positive effect on purchasing decisions. While the Service Quality Variable is also valid. Where service quality (X2) has a positive effect on purchasing decisions. This indicates that the better the brand iamge, the quality of service, it can be said that the purchase decision will increase.